The characteristic pulse frequency velocity at the end of the initial section jet - Исатаев, М.С.; Есеналиева, А.; Омаралина, А.; Молдабекова, Д.; Сейдулла, Ж.К. (Recent Contributions to Physics, 2016)
It is established that in the spectra of velocity pulsations in the initialphase axisymmetric jets with small thickness of the boundary layer in the outlet section of the nozzle, there are two of the most characteristicfrequency. One frequency is recorded on the boundary of the detachedjet in the boundary layer near the edge of the nozzle and the other at thejet axis at the end of the initial phase. The first is the occurrence of periodic perturbations as a result of loss of stability of free laminarboundary layer and depends on its thickness. The second characteristicfrequency due to the formation of large vortices with scale of order of the diameter of the jet in the initial section and does not depend on theinitial thickness of the boundary layer. The number of strugala calculated by the first characteristic frequencyis proportional to the square root of the Reynolds number. The same value of the Strouhal number calculated by the second characteristicfrequency keeps approximately constant value of S=0,4÷0,6.